The concept of time - Teichmann, Roger, 1963- (New York : St. Martin's Press, Scholarly and Reference Division, 1995)
Are past, present and future objective features of reality? What is an instant of time? Could time pass if nothing changed? In this book, the author attempts to show how considerations in the philosophy of logic and language are needed to settle these and other well-known issues. Part I deals with the debate over whether time is 'tensed' or 'tenseless'. Various problems are spelt out for the 'tenseless' view, and it is argued that the issue ends up hinging upon whether a genuinely tenseless language is conceivable. Part II has to do with periods and instants. The semantics of dates and of duration-terms are examined, and the notion of a durationless instant attacked. In Part III, the connections between time, change and causation are discussed. A criterial approach to the meanings of certain key temporal terms is adopted, yielding answers to a number of traditional metaphysical issues about time
1. McTaggart's Argument -- 2. Facts, Knowledge and Belief -- 3. Truth-Conditions -- 4. Dates and Units -- 5. Periods and Instants -- 6. Time and Change -- 7. The Direction of Time -- Appendix: The Notion of a Criterion: Wright's Objections
Includes bibliographical references (pages 191-194) and index
Keywords: Time; Time